Persistence of Dromiciops gliroides in landscapes dominated by Pinus radiata plantations - Sandra V. Uribe (Revista Chilena de Historia Natural, 2017)
Background: Monitos del monte (Dromiciops gliroides) are old-growth forest specialists and, thus, believed to be very sensitive to habitat transformation, although some recent studies show some level of plasticity of their habitat selection patterns. Findings: In this note we report on records of D. gliroides living in a very modified environment, composed mostly by industrial pine plantations and small fragments of Nothofagus spp. forests and we report the extension of the northernmost limit of its currently known distribution. Conclusions: Although highly reliant on native vegetation, Dromiciops gliroides has been able to persist in industrial forest landscapes dominated by pine plantations.